Damjeok Syndrome (U87.7): Significance of Its Inclusion in the KCD-9 and Contemporary Biomedical Perspectives - Chang-Gue Son; Seo-Hyung Choi (Journal of Korean Medicine, 2026)
Objectives: Damjeok syndrome (DJS) is a traditional Korean medicine–based clinical construct that was recently incorporated into the 9th revision of the Korean Standard Classification of Diseases (KCD-9) under code U87.7. This review summarizes the implications of the KCD-9 inclusion of DJS and discusses its significance and contemporary biomedical interpretation.Methods: Relevant literature regarding the proposed diagnostic framework of DJS, its clinical characteristics, and its relationship with conventional functional dyspepsia (FD) was reviewed. Recent biological findings potentially related to DJS were also examined.Results: DJS is defined by three core components: chronic unexplained dyspepsia, palpable upper abdominal hardness, and indigestion-associated systemic manifestations. Although DJS shares several clinical features with FD, it differs by incorporating a characteristic physical sign and a broader spectrum of systemic symptoms. Recent findings suggest possible associations with autonomic, neurochemical, and immune alterations, supporting its interpretation within the framework of gut-brain interaction. Upper abdominal hardness may represent a clinically observable sign linking gastrointestinal dysfunction with multisystemic manifestations.Conclusions: The inclusion of DJS in the KCD-9 provides an important opportunity to standardize its diagnostic framework and facilitate scientific investigation. DJS may also serve as a useful model for integrating traditional Korean medicine concepts with contemporary biomedical perspectives. Further studies are required to objectively characterize upper abdominal hardness and establish the biological validity and clinical utility of DJS.